Introduction to the Market Microstructure Symposium - Spatt, Chester S. (Review of Financial Studies, 1991)
The Market Microstructure Symposium in this issue of the Review of Financial Studies illustrates the diverse types of research being undertaken by scholars in this area of finance. The excitement and activity level reflect the overlap of a number of important ingredients, which in turn are helping to shape this subfield. The rational expectations paradigm provides a strong conceptual foundation for the theoretical analysis of problems. The development of the very powerful and tractable frameworks of Grossman and Stiglitz (1980), Glosten and Milgrom (1985), and Kyle (1985), and its extension by Admati and Pfleiderer (1988), has greatly spurred theoretical work in this area. In fact, the symposium includes the important extension of the Kyle framework to incorporate risk aversion in the Subrahmanyam (1991) article. The influence of these theoretical models of adverse selection has been enhanced by the broad recognition of the importance of adverse selection in actual security trading. The development of empirically tractable approaches for examining adverse selection [e.g., Glosten and Harris (1988)] has heightened the impact of the development of the theory. Admati (1991) provides a recent, more detailed overview of the theoretical literature on rational expectations and market microstructure.